Potential utilization of spent coffee waste in permeable concrete - Ching, Khong Sheh; Choo, Chin Siew (Bentham Science Publishers, 2024)
Concrete is widely used in the construction industry. A vast array of applications of concrete popularized permeable concrete due to its ability for sustainable climate resilient cities. In 2015, 17 Sustainable Development Goals were introduced by the United Nations. Among the 17 goals, goal 12: Responsible Consumption and Production, aimed at reducing reliance on natural resources to combat climate change, biodiversity loss, and pollution. Cement, being the most important material to cast permeable concrete, depletes natural resources while polluting the environment. Recent studies have utilized waste materials as permeable concrete materials to promote sustainable construction. With the increased consumption of coffee annually, this research investigates the use of Spent Coffee (SC) as partial cement replacement by weight in permeable concrete to reduce the environmental impact of cement production. This paper presents the chemical properties of SC wastes produced under different drying conditions through X-ray Fluorescence (XRF). Compressive strength and percolation rate of permeable concrete containing SC wastes as cement replacement at 0%, 1%, 3%, 5%, and 10% by weight are investigated at water-cement ratios of 0.3, 0.35, and 0.4. From the study, SC wastes are found possible to replace 1% by weight of cement with an optimum mix design of 0.35 w/c ratio. Aims: Permeable concretes are becoming increasingly used in the construction industry for the construction of climate-resilient cities. These concrete with permeable properties allow for use in open-air areas to improve percolation into the ground. However, casting requires the use of cement. Cement is one of the most destructive materials on earth. It is estimated that one pound of cement produces 0.93 pounds of carbon emissions, making up 7% of the world’s carbon emissions. To reduce this impact, coffee is aimed at reducing the use of cement in the permeable concrete mix. Spent coffee waste, is a waste that tends to be discarded as general waste into landfills. Nevertheless, studies on the use of spent coffee wastes as cement replacement in permeable concrete are scarce. Other than that, the effect of the different processing methods on the properties of spent coffee wastes was also not fully investigated. Hence, this study aims to identify the most optimum processing methods of spent coffee wastes to study its potential use as cementitious materials in permeable concrete to fill in this gap of knowledge and propose a lesser cement future. Background: Permeable concretes are popularized for their ability in the construction of climate-resilient cities. With the increased coffee consumption annually, this research investigated the use of spent coffee as partial cement replacement in permeable concrete to reduce the environmental impact of cement production, aligned with achieving the United Nations Sustainable Development Goals. Objective: The objective of this study is to first identify the potential of the spent coffee (SC) wastes as cement replacement. Then, to identify the best proportion of SC wastes as cement replacement by weight and the suitable water-cement (w/c) ratio for the permeable concrete mixes. Methods: First, SC wastes are processed with 4 different processes and examined through X-ray fluorescence analysis. SC permeable concretes are being casted at varying percentages and w/c ratio. A compressive strength test is then conducted. The percolation rate of the samples is obtained according to the falling head permeability test in the ACI 522R-10 report. Results: SC wastes were found to have the potential to be used as cement replacement. The findings revealed that SC at 1% by weight of cement replacement with a w/c ratio of 0.35, the permeable concrete demonstrated strength improvements with acceptable permeability properties compared to conventional mixes. Conclusion: From the study, it is concluded that SC wastes are possible to be used as cement replacement. The mechanical strength of the permeable concrete benefited from the incorporation of SC wastes while presenting acceptable permeability properties.